2015
DOI: 10.5430/jms.v6n2p70
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Commercialization Capability in Small and Medium-sized Businesses on Business Performances: Focused on Moderating Effects of Open Innovation

Abstract: This study aims to set the effects of technology commercializing capabilities (Acquisition / Internalization, market-oriented innovation, and exploitational innovation) on business performances (financial performance, non-financial performance, and innovational performance) as a primary model; examine the moderating effects of open innovation; build up the foundation to promote small and medium enterprises located in industrial complexes in Daegu; and lay groundwork for regional industrial strategies and natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Studies have shown that commercialization is positively correlated with competitiveness (Friedrichsen, Zarea, Tayebi, & Abad, 2017). Also, Seo, Kim and Choi (2015) observed that Korean SMEs with high commercialization capabilities continuously perform better than all their contemporaries. Hence, it was hypothesized that:…”
Section: Commercialization and Competitivenessmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies have shown that commercialization is positively correlated with competitiveness (Friedrichsen, Zarea, Tayebi, & Abad, 2017). Also, Seo, Kim and Choi (2015) observed that Korean SMEs with high commercialization capabilities continuously perform better than all their contemporaries. Hence, it was hypothesized that:…”
Section: Commercialization and Competitivenessmentioning
confidence: 98%
“…Commercialization includes all innovative activities in the marketing of ideas elicited from research and development (R&D), service development through ripened ideas, prototype processes and the development of new processes. This includes steps to improve the existing service processes using innovative technologies, and sales and marketing by developing new products and services (Li, 2012;Seo, Kim & Choi, 2015). Studies have shown that commercialization is positively correlated with competitiveness (Friedrichsen, Zarea, Tayebi, & Abad, 2017).…”
Section: Commercialization and Competitivenessmentioning
confidence: 99%
“…Small businesses in C2 substitute EO for TQM practices, while retaining goal setting and financial ratio analysis as core practices. In this scenario, organizations are more exploratory than efficiency driven (March, 1991;Seo, Kim, & Choi, 2015). These companies have goals and assess their achievement using financial ratios.…”
Section: C2 -Goal Setting Financial Ratio Analysis and Eomentioning
confidence: 99%